DISTRIBUTED DETECTION OF NODE CLONING ATTACKS WITH RANDOM WALK AND NETWORK DIVISION IN WIRELESS SENSOR NETWORKS - ZADA KHAN, WAZIR (2015)
Wireless Sensor Networks (WSNs) arc often deployed in unattended and harsh environments to perform various monitoring tasks. They arc susceptible to a wide variety of physical attacks typically node cloning attacks, also known as node replication attacks. Node Clone attack is an application independent attack and it is feasible due to the fact that sensor nodes arc typically unshielded. In this attack an adversary can easily capture and compromise sensor nodes and after replicating then1 the attacker may misinform the network by acknowledging them as legitimate nodes. These attackers may insert arbitrary number of clones or replicas into the network. ff these clones arc not efficiently detected, an adversary can further mount a wide variety of internal attacks which can cripple the various protocols and/or sensor applications. This thesis presents two novel distributed techniques called Random Walk with Network Division (RAND) and Single Stage Memory Random Walk with Network Division (SSRAND) for clone detection in WSNs which arc based on claimer-reporter-witness framework.